Effect of remimazolam tosilate on the incidence of hypoxemia in elderly patients undergoing gastrointestinal endoscopy: A bi-center, prospective, randomized controlled study - Liu, Fang; Cheng, Xiaoyan; Wang, Yingjie; Li, Kai; Peng, Tianliang; Fang, Ningning; Pasunooti, Kalyan K.; Jun, Seungho; Yang, Xiaomei; Wu, Jianbo (Frontiers in Pharmacology, 2023)
Background: Remimazolam tosilate is a new ultra-short-acting benzodiazepine sedative medicine. In this study, we evaluated the effect of remimazolam tosilate on the incidence of hypoxemia during sedation in elderly patients undergoing gastrointestinal endoscopy. Methods: Patients in the remimazolam group received an initial dose of 0.1 mg/kg and a bolus dose of 2.5 mg of remimazolam tosilate, whereas patients in the propofol group received an initial dose of 1.5 mg/kg and a bolus dose of 0.5 mg/kg of propofol. Patients received ASA standard monitoring (heart-rate, non-invasive blood pressure, and pulse oxygen saturation) during the entire examination process. The primary outcome was the incidence of moderate hypoxemia (defined as 85%≤ SpO2< 90%, >15s) during the gastrointestinal endoscopy. The secondary outcomes included the incidence of mild hypoxemia (defined as SpO2 90%–94%) and severe hypoxemia (defined as SpO2< 85%, >15s), the lowest pulse oxygen saturation, airway maneuvers used to correct hypoxemia, patient’s hemodynamic as well as other adverse events. Results: 107 elderly patients (67.6 ± 5.7 years old) in the remimazolam group and 109 elderly patients (67.5 ± 4.9 years old) in the propofol group were analyzed. The incidence of moderate hypoxemia was 2.8% in the remimazolam group and 17.4% in the propofol group (relative risk [RR] = 0.161; 95% confidence interval [CI], 0.049 to 0.528; p < 0.001). The frequency of mild hypoxemia was less in the remimazolam group, but not statistically significant (9.3% vs. 14.7%; RR = 0.637; 95% CI, 0.303 to 1.339; p = 0.228). There was no significant difference in the incidence of severe hypoxemia between the two groups (4.7% vs. 5.5%; RR = 0.849; 95% CI, 0.267 to 2.698; p = 0.781). The median lowest SpO2 during the examination was 98% (IQR, 96.0%–99.0%) in patients in the remimazolam group, which was significantly higher than in patients in the propofol group (96%, IQR, 92.0%–99.0%, p < 0.001). Patients in the remimazolam group received more drug supplementation during endoscopy than patients in the propofol group (p = 0.014). There was a statistically significant difference in the incidence of hypotension between the two groups (2.8% vs. 12.8%; RR = 0.218; 95% CI, 0.065 to 0.738; p = 0.006). No significant differences were found in the incidence of adverse events such as nausea and vomiting, dizziness, and prolonged sedation. Conclusion: This study explored the safety of remimazolam compared with propofol during gastrointestinal endoscopy in elderly patients. Despite the increased supplemental doses during sedation, remimazolam improved risk of moderate hypoxemia (i.e., 85%≤ SpO2 < 90%) and hypotension in elderly patients.